The locust standard brain: a 3D standard of the central complex as a platform for neural network analysis - El Jundi, Basil; Heinze, Stanley; Lenschow, Constanze; Kurylas, Angela; Rohlfing, Torsten; Homberg, Uwe (Frontiers in Systems Neuroscience, 2010)
Many insects use the pattern of polarized light in the sky for spatial orientation and navigation. We have investigated the polarization vision system in the desert locust. To create a common platform for anatomical studies on polarization vision pathways, Kurylas et al. (2008) have generated a three-dimensional (3D) standard brain from confocal microscopy image stacks of 10 male brains, using two different standardization methods, the Iterative Shape Averaging (ISA) procedure and the Virtual Insect Brain (VIB) protocol. Comparison of both standardization methods showed that the VIB standard is ideal for comparative volume analysis of neuropils, whereas the ISA standard is the method of choice to analyze the morphology and connectivity of neurons. The central complex is a key processing stage for polarization information in the locust brain. To investigate neuronal connections between diverse central-complex neurons, we generated a higher-resolution standard atlas of the central complex and surrounding areas, using the ISA method based on brain sections from 20 individual central complexes. To explore the usefulness of this atlas, two central-complex neurons, a polarization-sensitive columnar neuron (type CPU1a) and a tangential neuron that is activated during flight, the giant-fan shaped (GFS) neuron, were reconstructed three-dimensionally from brain sections. To examine whether the GFS neuron is a candidate to contribute to synaptic input to the CPU1a neuron, we registered both neurons into the standardized central complex. Visualization of both neurons revealed a potential connection of the CPU1a and GFS neurons in layer II of the upper division of the central body.